2011
DOI: 10.1111/j.1365-2095.2009.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary long-chain essential fatty acids on growth and stress tolerance in pikeperch larvae (Sander lucioperca L.)

Abstract: The nutritional requirements of pikeperch larvae have been sparsely examined. Dietary polyunsaturated fatty acids, arachidonic acid (ARA), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) may affect growth and physiological stress response in marine fish larvae, but these mechanisms have not received as much attention in freshwater fish. Pikeperch larvae were reared on Artemia from day 3 until 21 days posthatch. Artemia were enriched with six formulated emulsions, with inclusion of either fish oil, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 34 publications
(56 reference statements)
8
33
0
Order By: Relevance
“…). Various FA and phospholipids confer stress resistance in fish (Koven ; Lund & Steenfeldt ), although the mechanisms involved are still unclear. The modulation of cell membrane structure and/or function via diet‐induced changes in phosphoacylglycerol levels probably exerts major effects on fish physiology including a stress‐reducing action (Pavlidis et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). Various FA and phospholipids confer stress resistance in fish (Koven ; Lund & Steenfeldt ), although the mechanisms involved are still unclear. The modulation of cell membrane structure and/or function via diet‐induced changes in phosphoacylglycerol levels probably exerts major effects on fish physiology including a stress‐reducing action (Pavlidis et al .…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in other species have shown that de novo cortisol synthesis begins shortly after hatching, but a significant elevation in whole body cortisol in response to a stressor becomes obvious only days to weeks later, depending on the species (Barry et al 1995;Deane & Woo 2003;Szisch et al 2005). Various FA and phospholipids confer stress resistance in fish (Koven 2003;Lund & Steenfeldt 2011), although the mechanisms involved are still unclear. The modulation of cell membrane structure and/or function via diet-induced changes in phosphoacylglycerol levels probably exerts major effects on fish physiology including a stress-reducing action (Pavlidis et al 2011;Piccinetti et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the individual effects of DHA and EPA, the ratio of these two LC‐PUFAs in diets has also been demonstrated to exert significant influences on a range of physiological processes in marine fish (Ibeas, Cejas, Fores, Badía, Gómez & Lorenzo Hernández ; Rodríguez, Pérez, Díaz, Izquierdo, Fernández‐Palacios & Lorenzo ; Wu, Ting & Chen ; Dantagnan, Bórquez, Hernández & Izquierdo ; Trushenski, Schwarz, Bergman, Rombenso & Delbos ). However, its importance was relatively neglected compared to the total amount of n‐3 LC‐PUFAs (Sargent, Bell, Mcevoy, Tocher & Estevez ; Kim, Lee, Park, Bai & Lee ; Lee, Lee & Kim ; Skalli & Robin ; Hamre & Harboe ; Wilson ; Lund & Steenfeldt ; ØStbye, Kjær, Rørå, Torstensen & Ruyter ; Zuo, Ai, Mai, Xu, Wang, Xu, Liufu & Zhang ). The limited amount of work performed to date has suggested that dietary DHA and EPA had different efficiency in influencing bio‐functions of fish such as vision (Navarro, McEvoy, Bell, Amat, Hontoria & Sargent ; Noffs et al .…”
Section: Introductionmentioning
confidence: 99%
“…Besides the individual effects of DHA and EPA, the ratio of these two LC-PUFAs in diets has also been demonstrated to exert significant influences on a range of physiological processes in marine fish (Ibeas, Cejas, Fores, Bad ıa, G omez & Lorenzo Hern andez 1997;Rodr ıguez, P erez, D ıaz, Izquierdo, Fern andez-Palacios & Lorenzo 1997;Wu, Ting & Chen 2002;Dantagnan, B orquez, Hern andez & Izquierdo 2010;Trushenski, Schwarz, Bergman, Rombenso & Delbos 2012). However, its importance was relatively neglected compared to the total amount of n-3 LC-PUFAs (Sargent, Bell, Mcevoy, Tocher & Estevez 1999;Kim, Lee, Park, Bai & Lee 2002;Lee, Lee & Kim 2003;Skalli & Robin 2004;Hamre & Harboe 2008;Wilson 2009;Lund & Steenfeldt 2011;ØStbye, Kjaer, Rør a, Torstensen & Ruyter 2011;Zuo, Ai, Mai, Xu, Wang, Xu, Liufu & Zhang 2012b). The limited amount of work performed to date has suggested that dietary DHA and EPA had different efficiency in influencing bio-functions of fish such as vision (Navarro, McEvoy, Bell, Amat, Hontoria & Sargent 1997;Noffs et al 2009), pigmentation (Villalta et al 2008;Vizca ıno-Ochoa et al 2010) and reproduction (Mazorra, Bruce, Bell, Davie, Alorend, Jordan, Rees, Papanikos, Porter & Bromage 2003), whereas little information was available regarding the difference between DHA and EPA in modulation of fish health such as immunity and stress resistance (Wu, Ting & Chen 2003;Zuo, Ai, Mai, Xu, Wang, Xu, Liufu & Zhang 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies addressing larva resistance to stress have pointed out the relevance of highly unsaturated fatty acids (HUFA) to cope with the most common acute stressors found in hatchery daily operations such as netting (Lund & Steenfeldt, ), handling, air exposure (Atalah et al., ) and abrupt salinity changes (Rezek, Watanabe, Harel, & Seaton, ). The modulation of stress response by fatty acids may occur at different levels of the hypothalamus–pituitary–interrenal axis (HPI), and the effect of each dietary lipid profile tested varies greatly according to the specie, developmental stage and stressor tested (Montero & Izquierdo, ; Van Anholt, Koven, Lutzky, & Wendelaar Bonga, ).…”
Section: Introductionmentioning
confidence: 99%